Yeast immobilization in lignocellulosic wastes for ethanol production in packed bed bioreactor (2012)
ABSTRACT: This study is focused on the development of an immobilization process of yeast cells in waste lignocellulosic materials and their evaluation in the ethanol production by using packed bed bioreactors. We evaluated four different waste lignocellulosic materials: wood shavings, cane bagasse, corn cobs and corn leaves. The characterization made it possible to establish the microscopic structural differences between the four materials, as well as the differences in composition of lignin, cellulose, hemicelluloses and ash. A protocol for packaging materials and a quantification methodology of immobilized biomass was developed. An experimental design was conducted to determine the effects of the size of lignocellulosic materials on cell immobilization and to establish the effects of the flow rate in the immobilized cells when the fermentation is performed in packed bed bioreactors. Under the established experimental conditions we determined the size and flow rate that provided the better operational stability for the fermentation in packed bed bioreactor. The result of the study showed that the material in which the biggest amount of cells was immobilized was the sugar cane bagasse, and we obtained a value of 0.04657 dry immobilized biomass gX/gS (grams of dry biomass per grams of lignocellulosic material). This amount of immobilized biomass is significant compared to the values reported by other authors. As a result of the experimental design of the influence of flow and size of the carrier on the immobilization, it was established that there is no significant statistical difference in the range of the values used in the experiment (size of 3.4; 6.7 and 10 mm and flow rate of 0.36; 1.6 and 3.33 ml/s), so the best conditions for cell immobilization could be established taking into account the operational conditions and system stability. The size of the carrier selected was 3.4 mm and the flow rate of 0.36 ml/s. In the fermentations carried out in packed bed bioreactors with the biocatalyst (carrier + yeast), it was possible to obtain an increase of the amount of immobilized cells up to a value of 0.1444 ± 0.0061 grams of biomass after 12 hours of fermentation. Ethanol production using these biocatalysts reached a value of 20 g/L in 12 hours fermentation batch, equivalent to a volumetric productivity of 1.67 g/Lh. The results have established the implementation potential of ethanol production by continuous fermentation with immobilized cells in waste lignocellulosic materials.